Mortality Comparison of Using Anti Interleukin-6 Therapy and Using Standard Treatment in Severe Covid-19 - Sutadji, Jonathan Christianto; Widodo, Agung Dwi Wahyu; Indiastuti, Danti Nur (Folia Medica Indonesiana, 2021)
Severe Coronavirus Disease 19 (COVID-19) can cause serious lung inflammation and death. COVID-19 is characterized by a high mortality rate. This severity is associated with the overproduction of proinflammatory cytokines called